Incidencia de la motricidad gruesa en la técnica del voleo del servidor de los jóvenes de 17 años del Club de Ecua Vóley Profesionales Unidos de Babahoyo”, en el cantón Babahoyo, Provincia de Los Ríos, periodo 2021 - 2022 - Pacheco Paredes, Winston Elihu (2022)
The present investigation will be developed to verify the gross motor skills in the volleying technique of the server of the 17-year-olds of the Ecuavoley Club "Profesionales Unidos de Babahoyo", in the Babahoyo canton, province of Los Ríos, period 2021 - 2022. Research is considered non-experimental, because it is not possible to manipulate variables freely, but only natural situations are observed according to the problem under study. The modality will be applied to the research approach being quantitative. The type of design is research - action, in order to provide information that guides decision making. The methods used are theoretical and empirical level of knowledge. The techniques of basic research modality, bibliographic-documentary research and field research will be used. In addition, it will be developed using observation and survey techniques, where the survey will be carried out as a technique for collecting information, the questionnaire being its instrument for this technique. The population involved will be the 17-year-olds of the "United Professionals of Babahoyo" Club in the year 2021, from the information collected it has been verified that in the year 2021 there are approximately 46 young people, to whom a Probabilistic sampling will be applied, where a part of the population due to its randomness can be selected. Within the type of Probabilistic sampling, simple random sampling will be used, where the samples will be generated by random numbers, by computer, lottery or by placing the numbers in a jar.